A Gatekeeper Residue for NEDD8-Activating Enzyme Inhibition by MLN4924 - Julia I. Toth; Li Yang; Russell Dahl; Matthew D. Petroski (Cell Reports, 2012)
Inhibition of NEDD8-activating enzyme (NAE) has emerged as a highly promising approach to treat cancer through the adenosine sulfamate analog MLN4924. Here, we show that selective pressure results in HCT116 colorectal carcinoma cells with decreased MLN4924 sensitivity and identify a single-nucleotide transition that changes alanine 171 to threonine (A171T) of the NAE subunit UBA3. This reduces the enzyme's affinity for MLN4924 and ATP while increasing NEDD8 activation at physiological ATP concentrations. Expression of UBA3 A171T is sufficient to decrease MLN4924 sensitivity of naive HCT116 cells, indicating that it is a dominant suppressor of MLN4924-mediated cell death. Our data suggest that the on-target potency of MLN4924 selects for a point mutation in NAE that overcomes the molecule's inhibitory effects, allowing cancer cell survival.